Self-regulated approach to strategic learning (SRSL): a socio-cognitive perspective - Philip, Bromeley (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2005)
This paper explores one salient feature of socio-cognitive theory, enactive learning principle (Schunk, 2000, 2001; Elliot, Kratochwill, Cook and Travels, 2000). It will examine within the broader framework of en active learning principle, how successes attained as a consequence of one's actions (strategy use) in actual task performance generate cognitive motivation on the part of the learner, which in turn enhances the learner's sense of self-efficacy in those actions (using learning strategies) to self-regulate his/her learning process. When the learner becomes cognitively motivated, his/her level of self-efficacy also increases which then expands and develops his/her capacity for the acquisition of knowledge in metacognition that enables effective self-regulation of the learning process. Having possessed knowledge in metacognition, the learner tends to become self-regulated or strategic in his/her learning approach via strategic formulation and irnplementation of learning strategies in the learning contexts. Such learner is considered as a self-regulated learner who is capable of engaging strategic learning particularly in the context of academic reading. An understanding of how enactive learning principle informs the development of a self-regulated learner is at best theoretical unless some pragmatic mediation of the principle is made. The conceptualization of the SRSL Approach is an effort at pragmatically mediating theory into practice. The approach is designed by the author to provide a strategic processing framework for self-regulated learners to engage efficaciously in academic reading context. The paper will therefore attempt to expound some plausible effort at mediating a theoretical strand.